Comparative Analysis of the Radiology of Osteoporotic Vertebral Fractures in Women and Men: Cross‐Sectional and Longitudinal Observations from the Canadian Multicentre Osteoporosis Study (CaMos). (7th August 2017) - Lentle, Brian C; Berger, Claudie; Probyn, Linda; Brown, Jacques P; Langsetmo, Lisa; Fine, Ben; Lian, Kevin; Shergill, Arvind K; Trollip, Jacques; Jackson, Stuart; Leslie, William D; Prior, Jerilynn C; et al.
ABSTRACT: We compared two methods for osteoporotic vertebral fracture (VF) assessment on lateral spine radiographs, the Genant semiquantitative (GSQ) technique and a modified algorithm‐based qualitative (mABQ) approach. We evaluated 4465 women and 1771 men aged ≥50 years from the Canadian Multicentre Osteoporosis Study with available X‐ray images at baseline. Observer agreement was lowest for grade 1 VFs determined by GSQ. Among physician readers, agreement was greater for VFs diagnosed by mABQ (ranging from 0.62 [95% confidence interval (CI) 0.00–1.00] to 0.88 [0.76–1.00]) than by GSQ (ranging from 0.38 [0.17–0.60] to 0.69 [0.54–0.85]). GSQ VF prevalence (16.4% [95% CI 15.4–17.4]) and incidence (10.2/1000 person‐years [9.2; 11.2]) were higher than with the mABQ method (prevalence 6.7% [6.1–7.4] and incidence 6.3/1000 person‐years [5.5–7.1]). Women had more prevalent and incident VFs relative to men as defined by mABQ but not as defined by GSQ. Prevalent GSQ VFs were predominantly found in the mid‐thoracic spine, whereas prevalent mABQ and incident VFs by both methods co‐localized to the junction of the thoracic and lumbar spine. Prevalent mABQ VFs compared with GSQ VFs were more highly associated with reduced adjusted L1 to L4 bone mineral density (BMD) (–0.065 g/cm 2 [–0.087 to –0.042]), femoral neck BMD (–0.051 g/cm 2 [–0.065 to –0.036]), and total hip BMD (–0.059 g/cm 2 [–0.076 to –0.041]). Prevalent mABQ VFs compared with prevalent GSQ were also more highly associated with incident VF by GSQ (odds ratio [OR] = 3.3 [2.2–5.0]), incident VF by mABQ (9.0 [5.3–15.3]), and incident non‐vertebral major osteoporotic fractures (1.9 [1.2–3.0]). Grade 1 mABQ VFs, but not grade 1 GSQ VFs, were associated with incident non‐vertebral major osteoporotic fractures (OR = 3.0 [1.4–6.5]). We conclude that defining VF by mABQ is preferred to the use of GSQ for clinical assessments. © 2017 American Society for Bone and Mineral Research.